Coulson & Richardson's chemical engineering, J.M. Coulson and J.F. Richardson. Solutions to the problem in chemical engineering, volume 1 - Backhurst, J. R.; Harker, J. H. (John Hadlett), 1937-; Richardson, J. F. (John Francis); Coulson, J. M. (John Metcalfe). (Oxford : Butterworth-Heinemann, 2001)
This volume in the Coulson and Richardson series in chemical engineering contains full worked solutions to the problems posed in volume 1. Whilst the main volume contains illustrative worked examples throughout the text, this book contains answers to the more challenging questions posed at the end of each chapter of the main text. These questions are of both a standard and non-standard nature, and so will prove to be of interest to both academic staff teaching courses in this area and to the keen student. Chemical engineers in industry who are looking for a standard solution to a real-life problem will also find the book of considerable interest. * An invaluable source of information for the student studying the material contained in Chemical Engineering Volume 1 * A helpful method of learning - answers are explained in full.
Units and dimensions -- Flow of fluids - energy and momentum relationships -- Flow in pipes and channels -- Flow of compressible fluids -- Flow of multiphase mixtures -- Flow and pressure measurement -- Liquid mixing -- Pumping of fluids -- Heat transfer -- Mass transfer -- The boundary layer -- Momentum, heat and mass transfer -- Humidification and water cooling.
Keywords: Chemical engineering -- Problems, exercises, etc; Electronic books; Problems, exercises, etc